Analisis Kinerja Keuangan Bank Syariah Dengan Metode Economic Value Added (EVA) - Siagian, Yeni Aulia; Nawawi, Zuhrinal Muhammad; Syafina, Laylan (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2023)
The purpose of this study is to use the Economic Value Added (EVA) method to detail PT Bank Muamalat Indonesia's financial performance from 2016 to 2021.Secondary data are used in this qualitative descriptive study. The Economic Value Added (EVA) method was used to detail the time series financial data for 2016 to 2021 that was distributed by PT Bank Muamalat Indonesia via its official website, www.bankmuamalat.co.id. According to the study's findings, PT Bank Muamalat Indonesia achieved an EVA value of pounds (EVA > 0) in the years 2016, 2018, 2019, 2020, and 2021. This indicates that the bank was capable of increasing revenue and reducing costs. PT Bank Muamalat Indonesia, on the other hand, was unable to support bank fees or generate economic value addition in 2017 (EVA < 0).In addition, it is possible to assert that the EVA method is more successful in calculating the bank's financial performance.because the bank's value capital is taken into account by the EVA strategy.